N-acetylcysteine and Zn regulate corn yield - Nashriyah, Mat; Md. Sarwar, Jahan; Nurul, Munirah (Science Society of Thailand under Royal Patronage, 2015)
Glutathione (GSH), a non-protein molecule containing thiol groups affects plant growth and development. In this study, the effects of GSH on Zn-induced corn production were evaluated. Different Zn concentrations (0, 0.2, 1.5, and 3.0 ppm of Zn), with or without 100 µm of N-acetylcysteine (NAC), were arranged as a completely randomized design with 5 replications. Results show that neither NAC nor Zn affects plant height or leaf numbers. The treatment with NAC did not increase Zn-induced relative water content in leaves while enhancing Zn-induced photosynthesis rate (Pn ) and photosynthetically active radiation. Zn-induced chlorophyll (Chl) contents and Chl fluorescence (Fm) were increased by the NAC treatment. In addition, corn showed an improve yield and cob length in NAC-treated plants in the presence of Zn. Taken together, this study suggests that NAC might improve some physiological functions to enhance Zn-induced corn production.